CMP-3-deoxy-D-glycerol-D-galacto-nonulosonic acid (CMP-Kdn) synthetase: kinetic studies of the reaction of natural and synthetic analogues of nonulosonic acid catalyzed by CMP-Kdn synthetase - Terada, Takaho; Kitajima, Ken; Inoue, Sadako; Koppert, Klaus; Brossmer, Reinhard; Inoue, Yasuo (EJB, 1996)
In this report we present kinetic data of the activation reaction of several synthetic 3-deoxy-d-glycero-d-galacto-nonulosonic acid (Kdn) and N-acetylneuraminic acid (Neu5Ac) analogues catalyzed by the rainbow trout testis CMP-Kdn synthetase. This enzyme showed broad substrate specificity in terms of substitutions at C4 or C5 position of Kdn and Neu5Ac. In contrast, calf brain CMP-N-acylneuraminic acid synthetase had narrow substrate specificity, being active only on various N-acyl analogues of Neu5Ac and only slightly active on Kdn derivatives. Usefulness of the trout testis enzyme for synthesis of various CMP-sialate analogues, which could be donor substrates for sialyltransferases, was demonstrated.